Pengaturan Durasi Traffic Light pada Simpang Empat Kirab Kota Kupang Menggunakan Aljabar Max-Plus - Wadu, Mira (P3M- Politeknik Negeri Kupang, 2024)
The purpose of this study is to set the duration of traffic lights using max-plus algebra at the Kirab intersection in Kupang City. This study is based on the existing traffic light duration, then a directed graph is formed and modeled in max-plus algebra. Furthermore, the model is analyzed using the power algorithm and the average period of the green light duration for each phase is . In this study, the analysis results were obtained with . Thus, the new green light duration obtained using max-plus algebra for each intersection is 28 seconds, 31 seconds, 23 seconds and 30 seconds.